PERFORMANCE ANALYSIS OF UNSIGNALIZED INTERSECTION ON PERJUANGAN AND VETERAN STREET MARTAPURA BANJAR DISTRICT - Achmad Fajar; Yasruddin Yasruddin (Universitas Lambung Mangkurat, 2020)
The intersection of Jl. Perjuangan – Jl. Veteran is located in Martapura City, Banjar Regency, South Kalimantan Province. At this intersection there are only cautionary street lights or yellow lights, then the Intersection condition which is the road to residential areas, schools, shops, and traditional markets to support the occurrence of traffic jams and accidents Primary data or data taken from the field include geometric conditions, environmental conditions, side barriers, traffic volume at the Intersection of Jalan Perjuangan - Jalan Veteran Martapura City. Secondary data includes the number of residents in Martapura City and data on the growth of the number of vehicles. Furthermore, the data samples were analyzed using the Indonesian Road Capacity Manual (MKJI, 1997) to find out whether Intersection performance is still feasible or not. If the results of the analysis show that the Intersection performance is no longer feasible, it is necessary to solve the problem. At the intersection, Jl. Perjuangan - Jl. Veteran, Martapura City, Banjar Regency, on a unsignal condition, obtained a degree of saturation (DS) of 0.76 and delay (D) of all intersections of 12.7 seconds / smp with the Service Level Index at B, which indicates that at the intersection still has good conditions. After forecasting analysis, it is found that in the 6th year the degree of saturation (DS) is 1.11 and the whole delay is 26.21 seconds / smp with the Service Level Index in class D where the intersection has reached a bad condition or must be done intersection management analysis. By analyzing the form of intersection management when applied with a signalized intersection, the alternative 2 phase proposal is the best which is seen from the degree of saturation and delay with the value of Degree Saturation (DS) 0.74 and Delay (D) 18,33 seconds / smp with the intersection service level becomes C.